Leaching and Residual Kinetics of Oxytetracycline Incorporated Feed Treated to Juvenile Black Tiger Shrimp Penaeus monodon fabricious - Selvin, Joseph; A.P., Lipton (Fishery Technology, 2025)
The leaching rate of oxytetracycline (OTC)incorporated medicated feed after immersion in water was high during the first 10 min. About 56% of loss of OTC from the medicated feed was observed after 2 h of immersion, the leaching rate was not uniform in the 10 h experiment period. Juvenile black tiger shrimp Penaeus monodon fed for 7 days with 50-100 mg/kg shrimp of OTC were examined for residual accumulation and depletion. A residue of 3.47vig/g shrimp tissue was found after 1 day of post dosing. This concentration was estimated as 0.77% of the total OTC intake in the 7 days of experimental period. A substantial quantity of residue (1.56 ng/g) was observed up to 15 days of post-treatment. By the 20,h day of treatment, the OTC concentration was found in trace quantity (0.42 pg/g) or below detectable limit.